Building the scale of the scouting curriculum in the Ministry of Education from the point of view of the leaders who bear the wooden badge in Iraq - Haydar Einad; Nada Ismail (College of Physical Education and Sport Sciences, 2023)
The research aimed to build a measure of the reality of the scouting curriculum in the Ministry of Education, and the researchers followed the descriptive survey approach to suit it with the nature of the research. The General Directorates of Education and those affiliated to the Ministry of Education, and the research sample was chosen from (152) scout leaders. The researchers carried out the process of statistical analysis of the expressions of the scale to ensure the availability of the scientific conditions for the scale represented by the validity and reliability, and the researchers adopted the Likert method in building the questionnaire of the scale, and the scale consisted of (67) items, in the final form after the construction process.